The Personnel Question in the Tourism Industry: Who Wants What? - Ağbay, Nurulah Cihan (Fırat University, 2026)
This study aims to examine the meaning of the personnel problem discourse in the tourism industry and the expectations of involved actors. Based on a qualitative approach, the research examines online news articles highlighting personnel shortages in tourism together with the reader comments attached to them. The research data were collected through searches conducted on Google News. Within the framework of maximum variation sampling, the most-commented news items from different years were selected as units of analysis, and content analysis was applied to generate themes. The study produced two major findings. First, employers frame the personnel problem as an external issue, associating it with numerical labor shortages and the lack of qualified staff, and propose solutions through the employment of foreign workers and greater state support. Second, reader comments highlight internal organizational causes, such as low wages, nepotism, irregular working hours, labor rights violations, seasonality, and inadequate employee benefits. Comments portraying employees as ‘slaves’ and anticipating Generation Z’s stronger pursuit of rights constitute additional sub-findings of the study. The originality of this study lies in the reciprocal evaluation of the personnel problem in tourism through both news content and public commentaries.

Bu çalışmada temel amaç turizm endüstrisinde dile getirilen personel sorunu söyleminin ne ifade ettiğini ve aktörlerin ne istediğini araştırmaktır. Nitel yaklaşımın esas alındığı çalışmada, personel sorununa yer veren internet haberleri ve bu haberlere yapılan okuyucu yorumları karşılıklı incelenmiştir. Araştırma verisi Google Haberler üzerinden arama yapılarak toplanmıştır. Maksimum çeşitlilik örneklemesi kapsamında, farklı yıllara ait ve en çok yorum içeren haber içerikleri analiz birimi olarak belirlenmiş, bu verilere içerik analizi uygulanarak temalar geliştirilmiştir. Çalışmada iki temel sonuç ortaya çıkmıştır: (i) İşverenler turizmde personel sorununu sayısal yetersizlik ve nitelikli personel eksiği bağlamında işletme dışı faktörlerle ilişkilendirmektedirler. Çözüm için yabancı personel istihdamı ve devlet desteği talep edilmektedir. (ii) Haber yorumlarında personel sorununun, düşük ücret, kayırmacılık, düzensiz saatler, özlük hakları, mevsimsellik ve ek olanaklar gibi işletme içi faktörlerden kaynaklandığı vurgulanmaktadır. Yorumlarda, çalışanların köle olarak ifade edilmesi ve yeni kuşağın (Z kuşağı) hakkını daha fazla arayacağı beklentisi, araştırmanın diğer alt sonuçlarıdır. Turizmdeki personel sorununun hem haber içerikleri hem de kamusal yorumlarla karşılıklı olarak değerlendirilmesi araştırmanın özgünlüğüdür.
Turizm Endüstrisinde Personel Sorunu: Kim Ne İstiyor?
Keywords: Tourism Sociology; Turizm Sosyolojisi